The Influence of Price and Product Quality on Purchasing Decisions at Edelweis Florist Surabaya - Bahreisy, Mochammad Salim; Ikaningtyas, Maharani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of price and product quality on consumer purchasing decisions at Edelweis Florist Surabaya. Using a quantitative associative approach, data were collected from 153 respondents through purposive sampling and analyzed with multiple linear regression using SPSS. The findings reveal that price and product quality simultaneously exert a positive and significant effect on purchasing decisions. Partially, both variables also show a significant and positive influence. Price perceived as appropriate to product quality creates a balanced value perception, enhancing consumer attraction. Meanwhile, high product quality reflected in freshness, durability, and aesthetic design strengthens consumer confidence and increases purchasing intention. These results highlight that combining competitive pricing strategies with superior product quality significantly improves consumer decision-making. The study contributes theoretically to consumer behavior and marketing literature, while practically providing insights for florists to develop effective marketing strategies to maintain competitiveness in a dynamic market.